Pemodelan Tinggi Muka Air Gambut Berdasarkan Sifat Fisik Lahan Gambut: Modeling of Peat Water Table Depth Related to Physical Characteristics of Peatlands - Nur Febrianti (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 2018)
Peatland in Indonesia covers about 7% of the Indonesia land area. It also is facing some challenges especially related to land conversion and peat utilization. By law, utilization of peatlands can be done on specific peatland area and drainage canal is developed to lowering the water table. Therefore, the monitoring of peat water depth (TMA) should be established in order to minimize the negative impact of peatland utilization. However, to save time and cost it is necessary to have a model that can estimate the peat water table from its physical properties. The aim of this study is to develop a model for estimating TMA by using from the physical character of peatland. Then, it can be used as an early warning system to prevent fire that might occur. The confidence set of model was chosen by using the Akaike Information Criteria with a small sample sound (AICc). The results shows a confidence set of model consists of four models which includes bulk density at the depth of 0-50 cm, fiber content at the depth of 50-100 cm and the peat depth as model predictors. The model also showed a good agreement with the field measurement with the RMSE of 16.2 cm and R2 of 81%. This study suggests the critical peat water table depth to prevent fire is about 74 cm. Therefore, the condition of TMA should be maintained shallower than this level, otherwise the peat fire might occur.